CORPORAL PUNISHMENT AND ACADEMIC PERFORMANCE: A CASE STUDY IN SOUTHWESTERN MADAGASCAR - Whega Danitsaike Bien-Aimé; Ralaivao Hanginiaina Emynorane; Koto Bernard (Yayasan Nuraini Ibrahim Mandiri, 2025)
This study investigates the relationship between corporate punishment and academic performance in the southwestern region of Madagascar, where cultural traditions and official educational policies often stand in tension. The Ministry of Education formally prohibits physical discipline in schools, yet teachers and parents continue to use and defend it as a necessary tool for maintaining respect, order, and academic focus. Drawing on a qualitative approach, the study was conducted between 2023 and 2024 in Toliara I, Manombo, and Befandefa, involving 25 teachers, 30 parents, and 40 students aged 10 to 15 years. Data were collected through semi-structured interviews, classroom observations, and document analysis, then analyzed using thematic content analysis. The findings show that teachers often view corporal punishment as indispensable in resource-limited classrooms, parents especially in rural areas, perceive it as proof of care and responsibility, and students express ambivalence, recognizing both fear and increased compliance. The study highlights the contrast between international frameworks that condemn corporate punishment and local practices that legitimize it. It concludes that addressing this issue requires culturally sensitive interventions, greater investment in teacher training, and the development of practical alternatives to physical discipline. These results contribute new insights into the ongoing debate on education, discipline, and child rights in Madagascar.